Pengamanan Backup dan Restore Basis Data dengan Penambahan Enkripsi Advanced Encryption Standard (Studi Kasus: Analisis Jabatan Bagian Organisasi Kabupaten Balangan) - Bambang Abdi Setiawan; Nur Hamid Sutanto; Gusti F Rahman; Ema Utami; M Syukri Mustafa (Universitas Budi Darma, 2021)
Job analysis is needed to analyze and design what work to do, how to do it, and why the work should be done. Job analysis will provide information about job descriptions, job specifications, and job evaluations and can even predict job enrichment or expansion and job simplification in the future. This study aims to implement database security management procedures as a measure to prevent damage (error), loss and theft of data through backup and restore methods accompanied by encryption in the Job Analysis System application of the Balangan Regency Organization Division (Simanja). The backup process by adding Advanced Encryption Standard (AES) encryption which is stored to remote cloud hosting as a backup server using SSH Transfer Protocol (SFTP) provides adequate and efficient security.